Legal Protection in Providing Informed Consent for Obstetric Procedures - Anggrainy Dwifitriana Kouwagam; Hamzah Halim (Jurnal Kesehatan Masyarakat, 2026)
The purpose of this study is to inform that consent is a crucial part of medical procedures, particularly in obstetrics, serving as legal protection for both patients and medical personnel. International studies show that 44.7% of women in France did not provide consent before administering oxytocin in 2021, and in Indonesia, only 55% of patients fully understood their rights and informed consent procedures by 2024. This study aims to analyze the implementation of the law regarding informed consent in obstetric procedures and identify the legal barriers encountered. The  method used was normative legal research with a legislative approach and qualitative data analysis using NVivo. The results showed that although written consent procedures are widely implemented, the substance of the information provided is often not well understood by patients. The primary legal barriers identified were incomplete documentation, lack of patient understanding, and time constraints in medical emergencies. The study concluded that despite clear regulations, their implementation still faces significant obstacles. Recommendations include improving medical personnel’s understanding of the importance of clear communication, improving documentation, and providing legal training for patients. The recommendation of this study is the need to improve regulations and procedures to ensure more effective and comprehensive implementation of informed consent.